The Effect of Diet on Cardiovascular Disease, Heart Disease and Blood Vessels - Tada, Hayato (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cardiovascular disease (CVD), including coronary artery disease, heart disease, arrhythmias, and other types of vascular diseases, is one of the leading causes of death around the world. It is estimated that approximately half of the variabilities of CVD appear to be attributed to genetics. Therefore, the other half of them have been attributed to acquired factors, including diet. It is of note that even a genetic predisposition to CVD can be canceled out by a healthy lifestyle. In this regard, it is important to acknowledge that acquired factors, including diet, are causally associated with CVD. Based on these facts, important papers are presented in this Special Issue entitled "The Effect of Diet on Cardiovascular Disease, Heart Disease, and Blood Vessels".